Drug Monitoring Information System Development On Mother Medika Clinic Web Based: Drug Monitoring Information System Development On Mother Medika Clinic Web Based - Irfan Nurihsan; Fikri Akbar Falcata Winata (Jurnal Mantik, 2020)
Mother Medika Clinic is one of the entities that serve the general medicine (general practitioners and dentists), obstetric services, and service BPJS the diversity of services in the clinic persalinan.Seiring Mother Medika then providing medicines are increasingly banyak.Dengan diversity of services, then also increased the number of types and jumlahobat. Currently the process sales transactions, checks, and pencatatanobat drugs in the clinic is still done conventionally using a written form. In order to facilitate the clerk in the sale, checking, and inputting drugs,the author makes a drug monitoring information system on Mother Medika Clinic. Inidapat monitoring information systemdisplays drug stocks so as to enable staff to check the availability of the drug, drug sales transactions, displays incoming stock reports contain any notification regarding a new drug is added. And display reports the stock exit from transactions of sale of drugs